Écrire le corps dansant au xviie siècle : Ismâ‘îl Rusûkhî Anqaravî - Fabio Ambrosio (Revue des Mondes Musulmans et de la Méditerranée)
Ismâ‘îl Rusûkhî Anqaravî (m. 1041/1631), one of the most famous commentators of Djelâled-dîn Rûmî’s Mathnawî is both a defender and a profound interpreter of the practice of mystic dance (samâ‘). At a time in which controversy surrounding religious innovations (bid‘a) touched the visiting of holy tombs as well as the samâ‘, Anqaravî, ‚eyh of the Galata Lodge in Istanbul, undertakes the defense of the principal practice of the Whirling Dervishes (mawlawiyya, mevleviyye). An analysis of part of one of his works, the Minhâj’ul-fuqarâ, written in the Ottoman idiom and held as the manual of the Whirling Dervishes, leads to an in-depth study of the dancing body as the frontier between the sacred and the profane. The distinctions the author makes about the samâ‘ and the interpretation that he gives on it, particularly in two chapters of this work, furnish elements allowing a better understanding of a practice which puts the dervish’s body on stage. This theological study of Anqaravî represents an essay in writing the body in dance as a part of a cosmic motion that seeks to attain a uniting encounter with God.